Intrasphenoidal encephalocele: an incidental finding in emergency department - Waseem, Muhammad (Springer, 2013)
BACKGROUND: Basal encephaloceles are rare clinical entities. Intrasphenoidal encephalocele (ISE) is a rare form of basal encephalocele. The clinical presentation is often subtle and may remain undetected. Only a limited number of cases of ISE have been reported, mostly in middle-aged patients who presented with symptoms. Clinical diagnosis and management remain a challenge. Our case reports ISE as an incidental finding in a very elderly male patient. FINDINGS: We present a case of ISE discovered as an incidental finding in a 99-year-old male who presented to the emergency department (ED) after a fall from bed. The encephalocele was discovered in the evaluation of the computed tomography (CT) scan of the head. CONCLUSION: This is an incidental manifestation of a rare disease. It demonstrates that these encephaloceles may not manifest clinically or symptomatically as other reports have suggested.